Contract as Assumption and Consideration Theory: A Reassessment of Williams v Roffey Bros - Dawson, Francis (Victoria University of Wellington Law Review, 2011)
This article considers various aspects of the doctrine of consideration in the light of Professor Coote’s recent book "Contract as Assumption". Whilst a voluntary assumption of a legal duty is the essence of a contractual obligation, not every promise given in exchange for another promise with the intention to create legal obligations becomes enforceable in contract. Thus there is no contract where A promises to give property to B and B promises to accept it. The Law discriminates between promises given for value and promises which are illusory or gratuitous. It does so by examining the content of the counter-promise (in the above example B’s promise to accept) and requires that the performance of the obligation to be undertaken in the reciprocal promise confers a benefit on the promisor (in the example above A) or constitutes a detriment to the counter-party. It follows that whether a purported assumption of liability contained in a promise is enforceable is answered in our law by asking whether the promise is supported by consideration – for example whether what the counter-party has agreed to do is for the benefit of the promisor or to the detriment of the counter-party. It is also suggested that the concept of a practical benefit where an existing legal duty is sought to be modified has respectable historical antecedents which tend to support the reasoning in the controversial decision in Williams v Roffey Bros. Finally, Equity’s traditional reluctance to enforce a covenant made under seal which is not exchanged for value is re-examined, and the significance of recent statutory reforms adverted to.